Effectiveness of a training program for a patient with non-cardiac chest pain that combines intervention to improve quality of life, psychological state, and functional capacity: a case report - YILDIZ ÖZER, AYSEL (My University, 2023)
Background Noncardiac chest pain (NCCP) is persistent angina-like chest pain without cardiac origin that affects the patient’s health related quality of life (HrQoL), although it does not affect mortality. The effect of a comprehensive training program for NCCP focused on quality of life, psychological state, peripheral muscle strength, physical activity, and quality of life has not been previously established or published. Therefore, this study aimed to show the effectiveness of our combined training program that focuses on functional capacity, physical activity, pulmonary function, respiratory and peripheral muscle strength, dyspnea, fatigue, anxiety, and depression perception in NCCP patients with dyspnea. Case presentation A 38-year-old man with shortness of breath and NCCP was referred to to us for cardiopulmonary rehabilitation. Respiratory muscle strength (mouth pressure device), functional capacity (6 min walking test, 6-MWT), peripheral muscle strength (dynamometer), pulmonary function (spirometry), fatigue (fatigue severity scale), shortness of breath (MMRC, Modified Medical Council Research, Modified Borg Scale-MBS), physical activity (International Physical Activity Questionnaire, IPAQ), health related quality of life (SF-36, Short Form-36), and depression and anxiety (Hospital Depression and Anxiety scale, HADs) were assessed. Aerobic training combined with inspiratory muscle training (loading 30% maximal inspiratory pressure (MIP)) was administered at least 5 days/week for 6 weeks. Functional capacity, physical activity, pulmonary function, and respiratory and peripheral muscle strength improved, and dyspnea, fatigue, anxiety, and depression perception were decreased after the management. Conclusions This combined training program was effective for patients with NCCP and shortness of breath. Future studies should be conducted to find the most effective biopsychosocial training protocol for NCCP patients. Keywords Noncardiac chest pain, Quality of life, Functional capacity, Depression, Case report
Keywords: Sağlık Bilimleri; Fizyoterapi ve Rehabilitasyon; Health Sciences; Physical therapy and rehabilitation; Klinik Tıp (MED); Klinik Tıp; REHABİLİTASYON; Clinical Medicine (MED); CLINICAL MEDICINE; REHABILITATION; Fizik Tedavi, Spor Terapisi ve Rehabilitasyon; Kayropraktik; Rehabilitasyon; Physical Therapy, Sports Therapy and Rehabilitation; Chiropractics; Rehabilitation